algebra1

The equation: 6x-(x+3) =5+2x
First step in solving: 6x-x+3=5+2x
Write a clear explanation of what error has been made and what could be done to avoid the mistake.


The + 3 should be a -3.



should have been 6x-x-3=5+2x

if you have brackets with only a negative sign in front, imagine it is -1, then multiply each term inside the bracket by -1, just as if it were any other integer.

If you would like to be a regular volunteer homework help expert here, email me at Bobpursley

  1. 👍
  2. 👎
  3. 👁

Respond to this Question

First Name

Your Response

Similar Questions

  1. Chem 2

    Propane (C3H8) burns in oxygen to produce carbon dioxide and water vapor. The balance equation for this reaction is C3H8 + 5O2 ----> 4H20 + 3CO2. What volume of carbon dioxide id produced when 2.8 L of oxygen are consumed? Here

  2. Algebra 2

    To solve 49(3x) = 343(2x+1), write each side of the equation in terms of base what? . In the brackets are powers. I tried to solve this but I don't understand I believe it is the first base you go off from but I'm not sure what

  3. physics

    A bowling ball of mass 7.3 kg and radius 9.6 cm rolls without slipping down a lane at 3.4 m/s. Calculate its total kinetic energy. I tried this problem with the equation 3/4mv^2 but I did not get the correct answer, could I please

  4. Math Help

    An equation is shown below: 4(2x - 5) + 15 = 11 Write the steps you will use to solve the equation and explain each step. Can someone please explain step by step this equation? Thanks!!

  1. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

  2. Algebra

    Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A- step 4 B- step 1 C- step 2 D-

  3. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

  4. math

    What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

  1. math

    What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

  2. chemistry

    N2 + 3H2 --> 2NH3 how many grams of hydrogen are needed to react with 50 grams of nitrogen? Three moles of H2 per one mole of N2. How many moles of N2 is 50 grams? 1.79 moles is 50 grams. You do these problems in steps. Step 1.

  3. chemistry

    What is the percent ionization of a 1.38 mol/L weak acid if its Ka = 2.7 x 10-6? Answer to two (2) decimal places. I know what steps to use but have difficulty applying them to the quesiton Can someone please complete the question

  4. math

    (please solve step by step) solving equation (6x+2)/4 + (2x²-1)/(2x²+2) = (10x-1)/4x we got roots as

You can view more similar questions or ask a new question.